2020
DOI: 10.1002/er.5599
|View full text |Cite
|
Sign up to set email alerts
|

Performance of serpentine channel based Li‐ion battery thermal management system: An experimental investigation

Abstract: Thermal management of large-scale Li-ion battery packs is of great significance to their safety and life cycle, which would impact their applicability in electric vehicles. Of the many strategies developed for this purpose, indirect liquid cooling has already demonstrated quite high potentials in thermal regulation of such battery systems. In this study, a compact lightweight serpentine wavy channel configuration was chosen to construct an indirect liquid cooling system for a battery module of cylindrical Li-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Battery thermal management technology can be divided into air cooling [13][14][15][16][17][18][19][20], liquid cooling [21][22][23][24][25][26][27][28] and phase change material (PCM) cooling [29][30][31][32][33][34][35] according to different cooling media. Air cooling is one of the most common and widely used cooling methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Battery thermal management technology can be divided into air cooling [13][14][15][16][17][18][19][20], liquid cooling [21][22][23][24][25][26][27][28] and phase change material (PCM) cooling [29][30][31][32][33][34][35] according to different cooling media. Air cooling is one of the most common and widely used cooling methods.…”
Section: Introductionmentioning
confidence: 99%
“…The battery cooling under high temperature conditions and the battery heating function under low temperature conditions were experimentally studied. Reference [28] adopted an indirect liquid cooling system to cool the cylindrical lithium-ion battery module, performed various single-rate charge-discharge cycles on the battery, and simulated the working conditions of the battery under actual driving conditions. A comprehensive thermal analysis was carried out on the maximum temperature, the maximum temperature difference, and the percentage of heat storage.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the irregular channel type also be considered as a research factor, such as serpentine channel. Ibrahim et al [24] proposed a serpentine channel with a count of six mini-channels, and take the temperature, temperature difference, and the heat accumulation fraction as evaluation indicators, It has shown that the cooling ability is able to keep the battery pack within an appropriate temperature range for most cycling tests. Similarly, Zhang et al [25] proposed a snake-type channel with a guide plate, and the results show that this snake-type channel with a guide plate possessed better thermal exchange efficiency than an ordinary snake-type channel, thus could avoiding the heat accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…3,[11][12][13][14][15][16][17][18][19][20][21][22][23] At present, LIB is mainly used in mobile electronic equipment, and its application has begun to develop to the small size and lightweight of microelectrical appliances, as well as large electric equipment. [24][25][26][27][28] By contrast with traditional LIB materials such as LiCoO 2 , LiNiO 2 , LiMn 2 O 4 , LiFePO 4 , and so on. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] LiFePO 4 is a commonly used positive electrode material for power lithium-ion batteries, which has the advantages of high safety, but its specific energy is not high, so it is difficult to meet the needs of new energy vehicles with longer driving range.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium‐ion battery (LIB) is the best comprehensive rechargeable battery system software at this stage 3,11‐23 . At present, LIB is mainly used in mobile electronic equipment, and its application has begun to develop to the small size and lightweight of microelectrical appliances, as well as large electric equipment 24‐28 . By contrast with traditional LIB materials such as LiCoO 2 , LiNiO 2 , LiMn 2 O 4 , LiFePO 4 , and so on 29‐45 .…”
Section: Introductionmentioning
confidence: 99%